Implementation of Restorative Justice Towards the Criminal Act Aggravated Theft in The East Medan Sector Police - Sagita Ifani Emri; Abdul Rahman Maulana Siregar; Rahmayanti Rahmayanti (CV. Era Digital Nusantara, 2025)
This study analyzes the application of restorative justice to aggravated theft crimes at the East Medan Police Sector between January 2022 and June 2025. The approach used is a normative-empirical study with a juridical-sociological framework. The normative aspect examines Article 363 of the Criminal Code, Law Number 2 of 2002, Police Regulation Number 8 of 2021, Attorney General Regulation Number 15 of 2020, and Supreme Court Regulation Number 1 of 2024. The empirical aspect captures practices at the East Medan Police Sector through case data, interviews with investigators, victims, and perpetrators, as well as administrative documentation. The caseload under Article 363 has been relatively stable at 28 to 46 reports per quarter, with motorcycle theft accounting for 57 to 64 percent. Restorative justice facilitation is selectively implemented in 4 to 8 cases per quarter, with a success rate of 60 to 75 percent, and a resolution time of 18 to 21 days, faster than the typical 40-day transfer of files. Key criteria include voluntary consent from the parties, non-recidivists, restitution of losses, and a lack of public unrest. Cases involving violence, serious threats, or those that disrupt public security are not transferred to restorative justice and remain in litigation. Findings indicate that this restorative justice mechanism is effective for certain cases, consistent with the principle of ultimum remedium, reduces the burden of the judicial process, and increases party satisfaction. However, obstacles arise from differing perceptions among law enforcement officials, concerns about the deterrent effect, and inconsistent post-mediation monitoring. The study recommends strengthening SOPs based on eligibility indicators, mediation training for investigators, formal coordination with prosecutors and courts, involvement of community leaders, and post-settlement monitoring by Bhabinkamtibmas to prevent recurrence and maintain accountability.